Urbanisation beyond its core boundary and its impact on the communities in George Town conurbation, Malaysia - Samat, Malaysia; Mohd Amirul, Mahamud; Siti Masayu Rosliah, Abdul Rashid; Yassin, Elhadary; Hj. Mohd. Noor, Norzailawati (Malaysian Planning Institute, 2019)
Rapid urbanisation has raised major issues, especially in cities in developing nations. In Malaysia, for example, the urbanisation rate is at 74%, but the size of urban land is less than 10%. This phenomenon has caused urban expansion to encroach on to its fringe areas. At present, although much has been said about the economic benefits of urban expansion to the fringe areas, yet little is known about its impact on the local communities. This paper aims to highlight the spatial expansion of George Town Conurbation and to investigate how local inhabitants perceive urban development. This study used satellite images and GIS techniques to identify the spatial expansion of urbanisation in George Town. Quantitative and qualitative approaches of data collection were employed to investigate the impact of urbanisation on the communities. The findings indicated that the inhabitants in less urbanized states welcome urban expansion, as they perceive that urban growth generates more jobs and brings economic opportunities. On the contrary, those who have experienced a longer period of urban development did not fully welcome urbanisation. Therefore, inclusive development policies are required to ensure that urban growth will benefit dwellers in the urban area as well as in its surroundings. In addition, they are required to safeguard the environment.